The Effects of Various Types of Feed additives on The Chemical Composition of Local Chicken Meat (Gallus domestica). - Makmur, Ali; Sugito, Sugito; Samadi, Samadi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
Abstract. This study aims to determine the effect of giving various types of feed additives to the chemical composition value of super chicken chicken (Gallus domestica). This research is an experimental research using 20 super chicken chickens that come from chicken growth research (growth study). The design used in this study was Completely Randomized Design (RAL), consisting of 4 treatments and 5 replications. The treatment given was (A0 = control (Vita chick 0.7 gram / liter; A1 = 20 ml / liter probio-FM; A2 = 0.08% MOS-oligosaccharide / kg of feed and A3 = herbal leuser KI 5 ml / liter). is a 90 day old super chicken breast Chicken Variable observed moisture content, protein content and fat content The data obtained were analyzed by using vocabulary and tested further by Duncan's Multiple Range Test The results showed that treatment (P> 0,05) to the value of water content and protein of super chicken fowl.Average value of water content at each treatment A0 (69,81%), A1 (70,74%), A2 (71,56%) and A3 (71,52%) while mean value of protein A0 (18,95%), A1 (19,61%), A2 (19,01%) and A3 (19,14%)) P <0,05) to the fat content of super chicken flesh, mean of fat content were A0 (2.02%), A1 (1.49%), A2 (1.37%) and A3 (2.0%).Abstrak. Penelitian ini bertujuan mengetahui pengaruh pemberian berbagai jenis imbuhan pakan terhadap nilai komposisi kimia daging ayam kampung super (Gallus domestica). Penelitian ini merupakan penelitian experimen dengan menggunakan 20 ekor ayam kampung super yang berasal dari penelitian pertumbuhan ayam (growth study). Rancangan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL), terdiri dari 4 perlakuan dan 5 ulangan. Perlakuan yang diberikan adalah (A0 = kontrol (Vita chick 0.7 gram/liter; A1= 20 ml/liter probio-FM; A2= 0.08% MOS-oligosakarida/kg pakan dan A3= herbal leuser KI 5 ml/liter). Sampel penelitian adalah Daging dada ayam kampung super umur 90 hari. Variabel yang diamati kadar air, kadar protein dan kadar lemak. Data yang diperoleh dianalisis dengan menggunakan sidik ragam dan di uji lanjut dengan uji Duncan (Duncan’s Multiple Range Test). Hasil penelitian menunjukkan pemberian perlakuan tidak berpengaruh nyata (P>0,05) terhadap nilai kadar air dan protein daging ayam kampung super. Rataan nilai kadar air pada setiap perlakuan A0 (69,81%), A1 (70,74%), A2 (71,56%) dan A3 (71,52%) sedangkan rataan nilai kadar protein A0 (18,95%), A1 (19,61%), A2 (19,01%) dan A3 (19,14%). Perlakuan berpengaruh sangat nyata (P<0,05) terhadap nilai kadar lemak daging ayam kampung super. Rataan kadar lemak yaitu A0 (2,02%), A1 (1,49%), A2 (1,37%) dan A3 (2,0%).